Անդրկովկասի ներքին և արտաքին քաղաքական իրավիճակը (1917 թ. հոկտեմբեր - 1918 թ. փետրվար) - Պետրոսյան, Գեղամ (YSU Journal of International Affairs, 2016)
This article examines the issues of domestic and foreign policy of the Transcaucasian region. The Bolshevik Revolution in 1917 brought new conflicts in Russia, which pose a serious threat to the country's division. The February Revolution had rejected the monarchy, but at that time still did not represent a serious threat to the unity of Russia. The three Transcaucasian countries deepened internal conflicts caused by the external pressure of the Ottoman Empire. The Russian-Turkish war turned into a Turkish-Transcaucasian war.
Keywords: Transcaucasia, internal political situation, foreign policy situation, the Bolshevik coup, civil war, February revolution, Bolshevik extremism, negotiation process, militarypolitical situation